2007
DOI: 10.1124/mol.106.033746
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multivalent Ligand That Bridges the Allosteric and Orthosteric Binding Sites of the M2 Muscarinic Receptor

Abstract: THRX-160209 is a potent antagonist at the M 2 muscarinic acetylcholine (ACh) receptor subtype that was designed using a multivalent strategy, simultaneously targeting the orthosteric site and a nearby site known to bind allosteric ligands. In this report, we describe three characteristics of THRX-160209 binding that are consistent with a multivalent interaction: 1) an apparent affinity of the multivalent ligand for the M 2 receptor subtype (apparent pK I ϭ 9.51 Ϯ 0.22) that was several orders of magnitude grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 33 publications
1
68
0
2
Order By: Relevance
“…Given the structure of AC-42, it might behave as a bivalent ligand that derives considerable affinity through the interaction of its 1-(1-oxobutyl) -2-methylbenzene moiety with an ectopic site on the muscarinic receptor, while its 4-n-butylpiperidine residue interacts with the orthosteric site to compete with atropine. Such an inhibitory mechanism is consistent with the behavior of the allosteric ternary complex model [12]. A consideration of the two-state model provides predictions regarding the efficacy of AC-42 that could be used to distinguish between allosteric and bivalent ligand mechanisms.…”
mentioning
confidence: 54%
“…Given the structure of AC-42, it might behave as a bivalent ligand that derives considerable affinity through the interaction of its 1-(1-oxobutyl) -2-methylbenzene moiety with an ectopic site on the muscarinic receptor, while its 4-n-butylpiperidine residue interacts with the orthosteric site to compete with atropine. Such an inhibitory mechanism is consistent with the behavior of the allosteric ternary complex model [12]. A consideration of the two-state model provides predictions regarding the efficacy of AC-42 that could be used to distinguish between allosteric and bivalent ligand mechanisms.…”
mentioning
confidence: 54%
“…3,5 Such an approach has been successfully exploited to target GPCRs within the muscarinic acetylcholine receptor (mAChR) and adenosine receptor families. [6][7][8][9] In addition, recent studies have demonstrated that ligands that selectively target the M 1 and M 2 mAChRs may achieve their receptor-subtype-selectivity through a hitherto unappreciated bitopic mode of interaction. 10,11 One approach to explore the binding mode of bitopic ligands is to isolate both orthosteric and allosteric fragments from the parent structure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, although the M 1 mAChR-selective agonist N-desmethylclozapine was originally suggested to be allosteric, definitive evidence for an allosteric interaction with the receptor is lacking (10 -12). Moreover, novel bitopic ligands have recently been described, which concomitantly associate with both the orthosteric binding site and an allosteric binding site (13)(14)(15)(16)(17)(18)(19); it is possible that previous studies of selective agonists have classified such bitopic ligands as purely allosteric.…”
mentioning
confidence: 99%